Sintomas depressivos e relacionamentos conjugais: uma revisão sistemática da literatura - Cousseau, Jéssica (My University, 2019)
Depression is one of the most prevailing mental disorders in the world. It is associated with suffering and damage in several areas of life. Social relationships and the ability to manage day-to-day tasks are affected as well as marital relationships. The association between depression and the decline in the marital relationship is well documented in the literature, but the nature of this association is not always clear. The aim of this study is to understand how depressive symptoms impact a couple's relationship. A systematic review of literature was conducted, with searches in the Web of Science, Pubmed/ Medline and PsycINFO databases. The search included articles published between 2015 and 2019, in Portuguese and English. Only empirical studies which addressed predominantly depressive symptoms and marital relationships were considered. The results were analyzed based on the cognitive-behavioral perspective, in order to understand the impact of the cognitive, behavioral and emotional manifestations of the depressed subject in the conjugal relationship. The findings revealed an important role of the styles of communication, negative cognitive processes, support of the non-depressed spouse, two-way associations between depressive symptoms and marital dissatisfaction, and severity of depressive symptoms (sic).
A depressão é um dos transtornos mentais mais prevalentes no mundo. Está associada a sofrimento e prejuízos em diversas áreas da vida. Os relacionamentos sociais e a habilidade de administrar as tarefas do dia-a-dia são afetados, bem como os relacionamentos conjugais. A associação entre depressão e declínio no relacionamento conjugal é bem documentada na literatura, mas a natureza dessa associação nem sempre é clara. O objetivo desse estudo é compreender como os sintomas depressivos impactam o relacionamento do casal. Uma revisão sistemática da literatura foi conduzida, com buscas nas bases de dados Web Of Science, Pubmed/Medline e PsycINFO. A busca compreendeu os artigos publicados no período de 2015 a 2019, nos idiomas português e inglês. Apenas estudos empíricos e que abordassem predominantemente sintomas depressivos e relacionamentos conjugais foram considerados. Os resultados encontrados foram analisados à luz da perspectiva cognitivo-comportamental, buscando uma compreensão do impacto das manifestações cognitivas, comportamentais e emocionais do sujeito deprimido no relacionamento conjugal. Os achados revelaram um papel importante dos estilos de comunicação, processos cognitivos negativos, apoio do cônjuge não deprimido, associações bidirecionais entre sintomas depressivos e insatisfação conjugal e gravidade dos sintomas depressivos (sic).
Keywords: Depressão mental; Depressão mental - Diagnóstico; Depressão mental - Tratamento; Casamento; Psicoterapia conjugal; Casais - Aspectos psicológicos